Application of Genetic Algorithm for Economical Optimization of School Room Lighting According to SNI 03-6575-2001 - Uli Watini; Rudi Kurnianto; M Ismail Yusuf; Purwoharjono Purwoharjono (ELKHA : Jurnal Teknik Elektro, 2022)
The use of 24 and 30 FL for classrooms (9×8 m) and libraries (10×8 m), respectively, at SMP Negeri 25 Pontianak has not satisfied the lumen standard according to SNI 03-6575-2001. Replacing FL with LED requires calculation of budgets and lumen, including optimization of lamp distance configuration. Thus, replacing FL with LED through an adapted lumen of SNI 03-6575-2001 standard will need 15 and 20 lamps for classrooms and library, respectively. Later, the position of the LED placement has been optimized with the help of a genetic algorithm (GA) and drawing the lamp configuration using Dialux. Before optimization, the calculation result of luminaires for the classroom is 262 lux with a distance of x1 = 1.8 m and x2 = 2.67 m. After optimization, it is obtained that Eav = 283.513 lux and the distance between lamps x1 = 1.586 m and x2 = 2.67 m. The luminaire of library room before optimization is 322 lux, with a distance of x1 = 2 m and x2 = 2 m. After optimization the Eav is 384.9569 lux with x1 = 1.9119 m and x2 = 1.9 m. The lumen standard of replacing FL with LED has complied with SNI with cheaper procurement costs, i.e., for FL Rp.45,152,860.80 and for LED Rp.41,778,528.00 (saving Rp. 3,374,332.80).